The Contributing Factors of Delayed-Onset Post-traumatic Stress Disorder Symptoms: A Nested Case-Control Study Conducted After the 2008 Wenchuan Earthquake - Yang, Yanlin; Zeng, Wenqi; Lu, Bingqing; Wen, Jin (Frontiers in Public Health, 2021)
Background: Delayed-onset post-traumatic stress disorder (PTSD) after catastrophes is a big public health problem. However, good designs for revealing the PTSD among earthquake survivors are rare. This study was the first nested case-control study to explore the relationship between perceived social support and delayed-onset PTSD. Methods: A nested case-control study was conducted. Baseline (year 2011) and follow-up (year 2018) surveys were carried out to collect data. Those survivors met the criteria of positive symptoms of PTSD from the hardest-hit area were identified as the case group and PTSD-free survivors from the same area matched for age were defined as the control group, with a ratio of one to four. A conditional logistic regression was applied to evaluate the odds ratio (OR) of variables used in the study. Results: The unemployed quake survivors had a higher risk of developing delayed-onset PTSD (OR= 4.731, 95% confidence interval = 1.408 to 15.901), while higher perceived social support was a protective factor for suffering from delayed-onset PTSD (OR = 0.172, 95% confidence interval = 0.052 to 0.568). Conclusion: Delayed-onset PTSD after disasters could not be ignored. Active social support and the provision of stable job would contribute to maintaining the health of earthquake survivors.